THE IMPLEMENTATION OF ISLAMIC EDUCATION IN STUDENT MORAL GUIDANCE ON TRADITIONAL AND MODERN PESANTREN INSTITUTION - Sista, Taufik Rizki; Baqi, Safiruddin Al; Budiman, Agus (PEOPLE: International Journal of Social Sciences, 2019)
The Islamic education cannot be separated from moral guidance or moral education. Islamic boarding school institutions are the origin of Islamic education institution in Indonesia, the Pesantren institution is famous for its moral guidance for students. In the present day, there are two types of Pesantren institutions, the traditional and modern boarding schools, which both of them has its own characteristics in the practice of moral guidance for its students. This research is a qualitative research with case study models. The object of this research is Pondok Modern Darussalam Gontor campus 2 and Pondok Pesantren Darul Huda Mayak Ponorogo. The purpose of this study was to (1) find out how the Islamic Education models in Pondok Modern Darussalam Gontor campus 2 and Darul Huda Mayak Islamic Boarding School. (2) To find out how the moral guidance process in each Pesantren institution. The methodology of research use Qualitative Research by Case Study Model. The results of this study are (1) the models of religious education Carried out at Pondok Modern Darussalam campus 2 Refers to the curriculum of Kulliyatul Muallimin Al-Islamiyah where the coverage of knowledge is 100% religion and 100% scientific knowledge, while the implementation of religious education in the Darul Huda Islamic boarding school Mayak Refers to the principle of Salafi Hadistah, which is the education curriculum with traditional salaf and contemporary education methods. (2) The implementation of moral guidance activities at Pondok Modern Darussalam Gontor Campus 2 is to optimize the 24-hour education process based on the daily discipline and the school's curriculum.